Analytical reading in appointing women as judges - Hilal, Huda (The International Institute of Islamic Thought, 2011)
This research is trying to analyze the legal ruling of appointing woman as a judge through probing theoretical and practical concept in previous Islamic eras. It shows that judgment consisted of two essential points; Firstly, The knowledge in justice –mental ability-, Secondly, The force power –physical ability-. With the development of political systems the effective cause of judgment became knowledge in justice. Applying induction in Quranic verses shows that justice is essential objective must be maintained. This research distinguishes three doctrinal views, ranging from prohibition to permission in what to be allowed for testimony until absolute permissibility. It shows also problems in the central prophetic tradition, in verses inference, and analogical deduction.